2016
DOI: 10.1039/c6dt02445a
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule devices with graphene electrodes

Abstract: Several technological issues have to be faced to realize devices working at the single molecule level. One of the main challenges consists of defining methods to fabricate electrodes to make contact with single molecules. Here, we report the realization of novel spintronic devices made of a TbPc single molecule embedded between two nanometer-separated graphene electrodes, obtained by feedback-controlled electroburning. We demonstrate that this approach allows the realisation of devices working at low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 33 publications
(55 reference statements)
1
42
0
Order By: Relevance
“…A promising and fundamentally different approach was proposed in 2003 by Ishikawa and co-workers [14], who successfully demonstrated that slow magnetic relaxation could occur in mononuclear lanthanide complexes, such as those in which a lanthanide (Ln) ion is sandwiched between two phthalocyanine (Pc) ligands, (Bu4N)[LnPc2] (Ln = Tb III (1), or Dy III (2), Bu4N = tetrabutylammonium). This rather unexpected result marked the beginning of a new era in single-molecule magnetism, with many research groups investing a great deal of effort in trying to understand this behaviour [41][42][43][44][45][46][47]. Real progress has been made in determining which factors affect most significantly the spin dynamics of Ln-SIMs [17,48].…”
Section: Introductionmentioning
confidence: 99%
“…A promising and fundamentally different approach was proposed in 2003 by Ishikawa and co-workers [14], who successfully demonstrated that slow magnetic relaxation could occur in mononuclear lanthanide complexes, such as those in which a lanthanide (Ln) ion is sandwiched between two phthalocyanine (Pc) ligands, (Bu4N)[LnPc2] (Ln = Tb III (1), or Dy III (2), Bu4N = tetrabutylammonium). This rather unexpected result marked the beginning of a new era in single-molecule magnetism, with many research groups investing a great deal of effort in trying to understand this behaviour [41][42][43][44][45][46][47]. Real progress has been made in determining which factors affect most significantly the spin dynamics of Ln-SIMs [17,48].…”
Section: Introductionmentioning
confidence: 99%
“…From the previous discussion, it is clear that contact effects at the organic semiconductor/electrode junctions play a key role and a considerable effort is needed to properly engineer the properties of electrical contacts in short-channel architectures. Graphene and graphene-based materials have been recently considered as interesting electrode materials for field-effect devices based on organic semiconductors [98,99], graphene nano-ribbons [100], and single molecule junctions [101]. When used as electrode, graphene takes advantages of its intrinsic semi-metallic nature, in addition to its excellent mechanical and optical properties, and closing the technological gap in terms of sheet resistance and optical transparency [102] with the more common transparent electrodes, such as indium tin oxide and other carbon-based alternatives.…”
Section: Charge Transport Properties At Nano and Molecular Scale Of Pmentioning
confidence: 99%
“…1,2 It was recently demonstrated that stable electrode gaps below 5 nm can be formed using electroburning of graphene junctions. [3][4][5][6] Motivated by recent experimental progress in using such electrodes to probe transport through single molecules, 3,4,[7][8][9][10][11][12][13][14] theoretical studies have also focused on the electrical properties of graphene nanoconstrictions formed by incomplete electroburning of narrow graphene junctions. 3,[14][15][16][17][18] Graphene nanoribbons with zigzag edges have been predicted to show half metallic and spin filtering properties, 19,20 with high densities of states near the graphene Fermi energy, which are attractive for thermoelectricity.…”
Section: Introductionmentioning
confidence: 99%